2010
DOI: 10.1002/lsm.20917
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study to determine the safety and efficacy of a low‐energy, pulsed light device for home use hair removal

Abstract: This low-energy, pulsed-light device is a quick, safe, and relatively effective at-home hair reduction treatment option in patients with various skin phototypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 3 publications
0
28
0
Order By: Relevance
“…These seven prospective studies were evaluated for efficacy and adverse effects and are summarized in Table 2. One study was categorized as a CT 7 and six as UCTs 8–13 . A total of 24 studies were excluded because they did not assess the efficacy of light‐based home use devices according to our a priori methodological criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These seven prospective studies were evaluated for efficacy and adverse effects and are summarized in Table 2. One study was categorized as a CT 7 and six as UCTs 8–13 . A total of 24 studies were excluded because they did not assess the efficacy of light‐based home use devices according to our a priori methodological criteria.…”
Section: Resultsmentioning
confidence: 99%
“…All included trials evaluated short‐term (<6 months) hair reduction and one UCT 12 assessed long‐term hair reduction up to 12 months after treatment. Four of six short‐term studies 9–11,13 assessed the outcome at 3 months and two short‐term studies 7–8 evaluated outcome at 6 months after the final treatment. From Table 2 it is seen that the short‐term efficacy at 3 month follow‐up varied substantially, from 6% to 72% hair reduction (six studies), whereas more homogenous outcomes from 41% to 44% were reported at 6 month follow‐up (three studies).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumer-based treatments with portable home-based devices are rapidly evolving, and presently include low-level diode lasers and IPL devices [53,54]. Data support a transient short-term hair reduction from repetitive and continuous use with these low-level devices and the most prominent safety issue is regarding ocular damage [55].…”
Section: New and Alternative Treatment Strategiesmentioning
confidence: 99%